The Respiratory Induced Kidney Motion: Does It Really Effect the Shock Wave Lithotripsy? - Yucel, Mehmet Ozgur; Ozcan, Serkan; Tirpan, Gokhan; Bagcioglu, Murat; Aydin, Arif; Demirbas, Arif; Karakan, Tolga (Urology Journal, 2018)
Purpose: To investigate the effect of respiratory induced kidney mobility on success of shock wave lithotripsy (SWL) with an electrohydraulic lithotripter. Materials and methods: Between May 2013 and April 2015, 158 patients underwent SWL treatment for kidney stones with an electrohydraulic lithotripter. The exclusion criteria were presence of a known metabolic disease (such as cystinuria), non-opaque stones, need for focusing with ultrasonography, abnormal habitus, urinary tract abnormalities, and inability to tolerate SWL until the end of the procedure. Stones greater than 20 mm, and lower pole stones were also excluded. The movement of the kidneys were measured with fluoroscopy guidance. Results: The procedure was successful in 66.7% of the males, and 56.9% of the females. The mean stone size was 11 ± 3 mm in the successful group, and it was 14 ± 4 mm in the unsuccessful group. The mean stone mobility rate was 32 ± 10 in the successful group and 40 ± 11 in the unsuccessful group. Multivariate analysis showed that stone size and kidney mobility affected the success rate significantly, however Hounsfield Unit (HU) did not. Conclusion: The current study shows the significant effect of kidney motion on the success of SWL. Further studies with different lithotripters are needed to determine the significance of kidney mobility.